Celebrating Reform 2008 : Doing Business Case Studies - World Bank; International Finance Corporation (World Bank, Washington, DC, 2017)
Contents of the report are: introduction; by Penelope J. Brook, and Sabine Hertveldt; how to reform in 3 months. Azerbaijan registers businesses faster by setting-up a one-stop shop; by Svetlana Bagaudinova, Dahlia Khalifa, and Givi Petriashvili; one-stop shopping in Portugal; by Camille Ramos; competitiveness from innovation, not inheritance; by Karim Ouled Belayachi, and Jamal Ibrahim Haidar; harnessing the internet to streamline procedures; by K. Latha; creating a new profession from scratch; by Carolin Geginat, and Jana Malinska; how to raise revenues by lowering fees; by Jamal Ibrahim Haidar; when enough is enough; by Cemile Hacibeyoglu; slashing the time to register property from 18 months to 15 days; by Roger Coma-Cunill, and Marie Delion; bringing more credit to the private sector; by Valerie Marechal, and Rachel (Raha) Shahid-Saless; protecting minority shareholders to boost investment; by Jean Michel Lobet; giving a facelift to the Turkish tax system; by Caroline Otonglo, and Tea Trumbic; a public-private partnership brings order to Aqaba's port; by Doina Cebotari, and Allen Dennis; fighting entrenched interests to enforce judgments faster; by Lior Ziv; pragmatism leads the way in setting up specialized commercial courts; by Sabine Hertveldt; enforcing contracts quickly, with help from the neighbors; by Anthony Ford, and Oliver Lorenz; and repaying creditors without imprisoning debtors; by Mema Beye, and Joanna Nasr.